Paired boxed gene 1 expression: A single potential biomarker for differentiating endometrial lesions associated with favorable outcomes in patients with endometrial carcinoma. Issue 9 (26th May 2016) - Liu, Li‐Chun; Lai, Hung‐Cheng; Chou, Yu‐Ching; Huang, Rui‐Lan; Yu, Mu‐Hsien; Lin, Chi‐Pin; Tsai, Wen‐Chiuan; Chiang, Kai‐Jo; Wang, Yu‐Chi; Chao, Tai‐Kuang
Abstract: Aim: Paired boxed gene 1 ( PAX1 ) has previously been reported to be a methylation‐silenced gene in cases of cervical and ovarian cancers. We evaluated the expression of PAX1 in normal endometrium, endometrial hyperplasia and endometrial carcinoma (EC), and investigated the prognostic value of PAX1 expression in patients with EC. Methods: We conducted a hospital‐based retrospective review of PAX1 distribution immunohistochemically in 201 samples of endometrium from biopsy or hysterectomy. PAX1 immunoreactivity was classified into low and high score groups based upon the extent and intensity of staining. Results: There was intense intranuclear staining for PAX1 in premalignant endometrial lesions. A high PAX1 score was observed in a high percentage of samples of normal endometrium (93.3%), in endometrial hyperplasia without atypia (97.2%) and in endometrial atypical hyperplasia (87.5%), but this level was found in only one‐third of the EC samples (30.1%). The PAX1 protein score was significantly higher in samples of premalignant endometrial lesions compared with those of EC ( P < 0.001). Importantly, a higher PAX1 score in EC cases was correlated with good overall survival, with a hazard ratio of 0.22 for death (95% confidence interval, 0.05–0.96). Conclusions: PAX1 protein expression is a potential histopathology biomarker for the differential diagnosis of malignant and premalignant endometrial lesions. PAX1 is also a potential prognostic marker in cases of EC.